AGE DYNAMICS OF SPORTS ACHIEVEMENT IN HIGHLY QUALIFIED TRIPLE JUMP ATHLETES - T. Marinova (Trakia Journal of Sciences)
Commercialization of sport increasingly places elite athletes in a situation of choosing to participate in a greater number of competitions. On the other hand, sports specialists encourage young athletes in order to achieve a high sports result at an early age. This is one of the reasons that motivated us, based on an analysis of the dynamics of the sports result in the age aspect in elite triple jumpers, to propose a model of gradual increase of the result at different ages. The purpose of this study is to establish the optimal sports result for the individual ages in men’s triple jump. Tasks of the study: 1) To establish the optimal age for achieving the personal best by analyzing the achievements of 50 highly qualified triple jumpers. 2) To analyze the dynamics of the sports result in the age aspect of the same athletes. 3) Based on the obtained data, to propose a model of gradual increase of the result at various ages. Methods: To fulfill these tasks, we conducted a study of the literary sources and statistical analyzes of the results of the study individuals. We took the data for the analyzes from the worldathletics website. Results: The data analysis showed that the optimal age for achieving a personal result in the triple jump discipline for men is 24-25 years. Conclusions: The average values of the sports achievement of the individuals we analyzed in terms of age were used to create a recommended model for a gradual increase in the sports achievement, which can help to objectively plan the age dynamics of the sports result.